Assessing Levels of Domestic Violence among Secondary-School Students in Al-Nasiriya City/ Iraq - Maan Hameed Ibrahim Al-Ameri (Journal of Global Pharma Technology, 2016)
Introduction: Violence is the intentional use of physical force against oneself, another person, or groups that result in injury, death, psychological harm, mal-development or deprivation(1). Domestic violence (also named domestic abuse or family violence) is a pattern of behavior which involves violence or other abuse by one person against another in a domestic setting. Child exposure to domestic violence constitutes a prevalent concern nationwide. Over 15 million children are estimated to live in households in the U.S. in which at least one incident of physical domestic violence has occurred in the previous year. Lifetime of childhood exposure rates to physical domestic violence in the U.S. have been projected at approximately 16% (2). Family violence described by the law on protection and treatment of child abuse in the United States which was issued that the abuse and neglect. Minimum is any act of talk or failed to act the part of a parent or caregiver that result in death, harm physical, verbal violence, emotionally dangerous, sexual abuse, sexual exploitation and any act or failure to act resulting in imminent danger of serious harm(3). Objectives: The purpose of the study is to assessing levels of domestic violence among secondary-school students in the Al-Nasiriya city and to find out any association between levels of domestic violence and some demographic characteristics. Methodology: A descriptive study was achieved from October, 20th, 2017 to July, 1st, 2018. A non-probability (purposive) sample of 600 students with age ranged between12 and 18 year was chosen from ten secondary schools (simple random sampling). A designed questionnaire was used for the study and it consists of two parts: part one contains demographic characteristics of the students which include age, gender, class, residency, income, house, level of education and occupation of father and mother, number of kids and order of kid; part two is the scale domestic violence (Zahra Abdel-Hamezah Hadi, 2013). This part is composed of (39) item and is divided into (3) sections domains; they are verbal violence which is composed of (10) items; Physical violence which is composed of (13) items and psychological violence which is composed of (16) items. The statistical analysis was achieved by using the descriptive statistics: frequency, percentage, distribution and inferential analysis such as Chi2. Results: Six hundred questionnaires were completed. 60.0% of sample is intermediate. 66.8% of sample is male, 25.3% of the students are in first class, 78.8% of sample is city, 46.3% of sample is monthly income almost enough, 27.7% of father is secondary graduate and 42.5 of mother is illiterate, 60.2% of sample occupation of father is free work and 88.7% of mother is house keeper. The severity of domestic violence of the participants ranged from mild 54.7% of the verbal violence; moderate 39.3% of physical violence; and mild 34.2%of psychological violence. Conclusion: The present study revealed that more than half of student are intermediate, and also more than half of the student are male, less than half of student are first class, more than half of student are city, less than half of income are almost enough, less than half of education father are secondary graduate and mother education are illiterate, more than half job of father are free work and job of mother are house keeper. 54.7% more than half of student are verbal violence, 39.3% less than half of physical violence and 34.2% of psychological violence. Recommendation: Necessity to provide for the services rehabilitation victims of domestic violence by supporting the role of social researcher in school and at home. Intensifying programs related to family guidance in order to increase family awareness through the various media. Urge concerned parties to establish laws legislation and deterrent systems to deal with cases of domestic violence. To spread awareness among the members of the community about the seriousness of this phenomenon.Keywords: Domestic violence, Student, School, Nasiriya city.